Performance Analysis of Axial Flow Compressor and Part Load Consideration in a Gas Turbine Application - Majid ASLI; Abolghasem M. TOUSI (Journal of Thermal Science and Technology, 2013)
A performance analysis of a three stage axial flow compressor with part load consideration in gas turbine application regarding surge margin is presented in this paper. A three stage compressor was designed and numerical simulation as well as a modified stream line curvature analysis was applied to validate the design model. These two analyses verified the design which was based on a test case model and showed an acceptable accuracy. Performance was predicted by introducing a modified one dimensional method for the compressor. A typical gas turbine with specific components was considered to evaluate the effect of compressor early design parameters on its behavior at part loads. Four compressors were designed with change in reaction ratio and flow coefficient as the input data of the design process. The analysis showed that an increase of 8% and decrease of 5% in reaction ratio and flow coefficient respectively, compared with the base design model, would lead to getting away the running line from the surge line by an amount of 5% approximately and working in a safer margin as well as higher efficiency working range, so the energy conversion can be done efficiently.